The Kuzari and the shaping of Jewish identity, 1167 - 1900 - Shear, Adam (Cambridge Univ. Press, 2008)
Texts and contexts: premodern dissemination and transmission -- The image and function of the Kuzari in the late Middle Ages -- The Kuzari in Renaissance Italy -- Judah Moscato's project and the making of an authoritative work -- The image and function of the Kuzari in early modern Europe -- The creation of an Enlightenment Kuzari -- Continuity and change in the nineteenth century -- Conclusion: The emergence of late modern dichotomies